Arab Mediterranean youth's values: The role of values and value congruence on intentions to Emigrate. (March 2023) - Sortheix, Florencia M.; Weber, Wiebke; Lilleoja, Laur; Anna Renvik, Tuuli; Sánchez-Montijano, Elena
Abstract: This paper analyses the role of personal values, value congruence and intentions to emigrate among Middle East and North Africa (MENA) youth. We use a survey data set ( N  = 8.087) from Algeria, Egypt, Lebanon, Morocco, and Tunisia, collected among respondents aged 15–29. Results showed that beyond demographic characteristics, such as being male, highly educated and not having a job, personal values predicted higher chances of reporting intentions to emigrate. Logistic regression results showed that stimulation and achievement values predicted higher, and tradition values predicted lower chances of reporting intentions to emigrate. Furthermore, value congruence (i.e., having similar values as those of most of their co-nationals) was related to lower chances of reporting intentions to emigrate. These results support the notion that those who intend to emigrate differ from their co-nationals in terms of value priorities. We discuss the policy implications of our findings. Highlights: The study uses a unique sample of about 10.000 young individuals from Algeria, Egypt, Lebanon, Morocco, and Tunisia. Individuals who reported high stimulation and achievement values, and low tradition values were more likely to intend to emigrate from the country in the next 5 years. Value (in)congruence was related to higher likelihood of reporting intentions to emigrate, those who held different values than the majority in their group of co-nationals wish to move away.